Jurisprudential-legal evaluation of the use of loans based on oil and gas reserves (RBL) in the upstream segment of the petroleum industry - Seyyed Amir Hossein Etesami; Amir Sadeghi Shahdani; Maqsud Imani (جستارهای اقتصادی, 2021)
Financing is one of the most basic requirements for development and production projects in petroleum reservoir. The specific characteristics of oil projects limit the optimal financing methods to the specific conditions of this industry. The exploration and production (E&P) stages of oil and gas reservoirs impose a higher risk on the oil contractor than the production stage. Therefore, in the exploration phase, the contractor tends to share the risk and issue shares. But in the process of development and production, the method of borrowing and lending is used. Loans based on reserves are a unique method of financing oil companies in the phases of reservoir development and production. In this method, the oil company can use bank facilities in the form of a loan up to a peculiar limitation (borrowing base) determined based on the reservoir under the possession of the oil company. The use of this method depends on the conditions and restrictions of possession in oil reservoir. In this paper, the feasibility of using the above-mentioned financing method was discussed from the point of view of Islamic jurisprudence (Fiqh) and law.